Elaboración del estudio de prefactibilidad para el montaje de la línea de producción y comercialización de Tilapia Roja en la empresa SO (2017)
The company SO (located in Campoalegre, Huila) has historically used its land to grow rice; However, due to fluctuations in the price of this grain, the arrival of difficult-to-manage pests and the increase in the dollar, which has a direct impact on the costs of imported and imported fungicides, have led to The cultivation of this product is not so profitable. For these reasons the SO company decided to diversify its crops by planting maize, sorghum, cotton, watermelon and ahuyama, according to the market opportunities, but not with the same profitability and output of the product. Therefore, the opportunity to create a business line related to the production and distribution of Red Tilapia is raised.